Corrosion-resistant castable and its preparation method
Patent Information
- Application Number
- CN202611443630.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-20
AI Technical Summary
然而,长期工业实践表明,传统水泥结合耐侵蚀浇注料存在先天性性能缺陷,主要体现在:(1)高温抗渣侵蚀与抗渗透性能不足:铝酸盐水泥在高温下分解生成低熔点钙铝酸盐,于基质中形成连续液相,显著降低材料高温强度与抗渣侵蚀性能
(1)本发明所述的耐腐蚀浇注料,以不同粒径的废弃刚玉-尖晶石耐火浇注料配合物以及少量的0.088mm<粒度≤1mm的预处理含钛高炉渣作为骨料,以粒度≤0.088mm的预处理二次铝灰以及预处理含钛高炉渣作为粉料,以锆酸钙、铝酸铈以及钽酸镧的配合物作为抗渣剂,以ρ-Al2O3微粉以及拟薄水铝石粉的配合物作为无水泥结合剂,以柠檬酸作为缓凝剂,氧化锆用于改善材料热震稳定性,聚丙烯防爆纤维作为防爆组分,聚羧酸减水剂用于改善浇注料施工流动性,降低成型加水量,由此,原料之间相互配合,使得制备的浇注料在服役过程中具备优异的高温强度以及耐侵蚀性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of castable preparation technology, specifically relating to a corrosion-resistant castable and its preparation method. Background Technology
[0002] Castable refractories, also known as refractory castables, are a type of unshaped refractory materials composed of refractory aggregates, powders, binders, and functional additives. Due to their excellent comprehensive performance, refractory castables have been widely used in high-temperature industrial kilns and equipment in metallurgy, building materials, chemical industry, power industry, and other fields. They are the core basic materials for ensuring the stable operation of high-temperature industrial equipment.
[0003] In the field of metallurgical blast furnaces, refractory castables are mainly used in key high-temperature parts such as the blast furnace body, tapping area, main slag trough, skimmer, and slag trough. Among them, the skimmer, located at the end of the main slag trough, is the core component for achieving precise slag-iron separation and operates under the most demanding conditions. This component is constantly exposed to a high-temperature environment of 1300℃-1550℃, continuously enduring the strong mechanical erosion of high-temperature molten iron and slag, complex high-temperature chemical corrosion, and thermal shock from frequent temperature changes. This places extremely high demands on the high-temperature strength, structural density, slag erosion resistance, and impermeability of the castable used. Its corrosion resistance and service life directly determine the blast furnace's iron tapping efficiency and continuous production capacity.
[0004] At present, blast furnace skimmers generally use traditional alumina-silicon carbide-carbon aluminate cement-bonded castables. This type of castable uses high-quality brown corundum and high-alumina bauxite clinker as aggregates, silicon carbide as wear-resistant and oxidation-resistant components, and carbonaceous materials as anti-slag wetting and thermal shock buffer components. It relies on aluminate cement to achieve room temperature hardening and molding. However, long-term industrial practice has shown that traditional cement-bonded erosion-resistant castables have inherent performance defects, mainly reflected in: (1) Insufficient high-temperature slag erosion and anti-permeability performance: Aluminate cement decomposes at high temperature to generate low-melting-point calcium aluminate, forming a continuous liquid phase in the matrix, which significantly reduces the high-temperature strength and slag erosion resistance of the material. (2) Although silicon carbide can improve wear resistance and thermal conductivity, it is easily oxidized in the oxidizing atmosphere during the iron tapping interval to generate silica glass phase, which then reacts with calcium oxide and alumina in the matrix to form low-melting-point silicates, which increases the amount of high-temperature liquid phase.
[0005] Therefore, it is necessary to explore a new type of corrosion-resistant castable that combines slag erosion resistance, impermeability resistance, and high-temperature structural stability. Summary of the Invention
[0006] The purpose of this invention is to provide a corrosion-resistant castable that exhibits good high-temperature strength and slag resistance during service. In addition, this invention also provides a method for its preparation.
[0007] The corrosion-resistant castable of the present invention is composed of the following raw materials in parts by weight: 13-15 parts of waste corundum-spinel refractory castable with a particle size of 8mm < ≤ 15mm, 15-17 parts of waste corundum-spinel refractory castable with a particle size of 5mm < ≤ 8mm, 14-16 parts of waste corundum-spinel refractory castable with a particle size of 3mm < ≤ 5mm, 12-14 parts of waste corundum-spinel refractory castable with a particle size of 1mm < ≤ 3mm, 9-11 parts of waste corundum-spinel refractory castable with a particle size of 0.088mm < ≤ 1mm, and 0.088mm < ≤ 1mm. The pretreatment process includes 5-7 parts of titanium-containing blast furnace slag, 4.5-5.0 parts of titanium-containing blast furnace slag with a particle size ≤0.088mm, 8.5-9.5 parts of secondary alumina ash with a particle size ≤0.088mm, 1.9-2.1 parts of calcium zirconate, 1.5-1.7 parts of cerium aluminate, 1.3-1.5 parts of lanthanum tantalate, 5.3-5.7 parts of p-Al2O3 micro powder, 2.7-3.1 parts of pseudoboehmite powder, 0.04-0.05 parts of citric acid, 0.22-0.24 parts of polypropylene explosion-proof fiber, 2.7-3.1 parts of zirconium oxide, and 0.18-0.23 parts of polycarboxylate superplasticizer.
[0008] The waste corundum-spinel refractory castable, by mass percentage, has the following chemical composition: Al2O3 83.98%, MgO 10.32%, SiO2 2.09%, Fe2O3 0.95%, Na2O 0.87%, CaO 0.81%, K2O 0.04%, SO3 0.02%, and loss on ignition 0.92%.
[0009] The preparation method of pretreated titanium-containing blast furnace slag consists of the following steps: crushing the titanium-containing blast furnace slag to a particle size ≤15mm, removing iron through magnetic separation, then placing it in an air-atmosphere resistance furnace, heating it from room temperature to 800℃ at a heating rate of 5℃ / min and holding it at that temperature for 1h, cooling it to room temperature with the furnace, and preparing the pretreated titanium-containing blast furnace slag by two-stage sieving: 0.088mm < particle size ≤1mm and particle size ≤0.088mm.
[0010] Wherein: the titanium-containing blast furnace slag is an industrial solid waste generated during the smelting of vanadium-titanium magnetite, and its chemical composition by mass percentage is as follows: CaO 28.02%, SiO2 22.54%, TiO2 21.62%, Al2O3 14.10%, MgO 10.03%, FeO 1.31%, MnS 1.26%, V2O5 0.72%, and loss on ignition 0.40%.
[0011] The preparation method of pretreated secondary aluminum ash consists of the following steps: ① The secondary aluminum ash is placed in an air-atmosphere resistance furnace and heated from room temperature to 1050℃ at a heating rate of 5℃ / min, and held at that temperature for 2.5h, and then cooled to 25℃ with the furnace; ② The cooled calcined product is added to hot water at 85℃ with a solid-liquid mass ratio of 1:2.5, and stirred for 100min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ③ Hot water at 85℃ is added to the filter cake obtained in step ② with a solid-liquid mass ratio of 1:2.5, and stirred for 75min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ④ Hot water at 85℃ is added to the filter cake obtained in step ③ with a solid-liquid mass ratio of 1:3.0, and stirred for 80min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ⑤ The filter cake obtained in step ④ is dried at 110℃ under forced air for 12h, and then passed through a 180-mesh sieve to prepare pretreated secondary aluminum ash.
[0012] The secondary aluminum ash, by mass percentage, has the following chemical composition: Al₂O₃ 86.32%, MgO 8.42%, SiO₂ 1.34%, CaO 1.00%, K₂O 0.88%, Fe₂O₃ 0.29%, MnO 0.28%, Na₂O 0.24%, P₂O₅ 0.11%, TiO₂ 0.13%, and loss on ignition 0.99%.
[0013] The method for preparing the corrosion-resistant castable of the present invention comprises the following steps: (1) Waste corundum-spinel refractory castable with particle size ≤ 15mm, waste corundum-spinel refractory castable with particle size ≤ 8mm, waste corundum-spinel refractory castable with particle size ≤ 5mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, and waste corundum-spinel refractory castable with particle size ≤ 0.088mm. Waste corundum-spinel refractory castable recycled material and pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm are added to a forced mixer and dry-mixed for 80-90s to ensure uniform mixing. Then, pretreated secondary alumina ash with a particle size of ≤ 0.088mm and pretreated titanium-containing blast furnace slag with a particle size of ≤ 0.088mm, calcium zirconate, cerium aluminate, lanthanum tantalate, p-Al2O3 micro powder, pseudoboehmite powder, zirconium oxide, citric acid and polycarboxylate superplasticizer are added and dry-mixed for 1.5-2.0min. Finally, polypropylene explosion-proof fiber is added and dry-mixed for 20-30s to prepare a dry mixture. (2) Add deionized water to the dry mixture prepared in step (1) and continue stirring for 3-5 minutes to obtain the casting slurry; (3) The prepared grout is injected into the precast mold, placed on a vibrating table for vibration molding, then allowed to stand for curing, and finally demolded. (4) The demolded preforms are sent into a baking kiln for segmented gradient baking. First, the temperature is raised to 110℃ at a heating rate of 0.8-1.0℃ / min and held for 12-14h. Then, the temperature is raised to 220℃ at a heating rate of 1.0-1.2℃ / min and held for 6-8h. After that, the temperature is raised to 450℃ at a heating rate of 1.3-1.5℃ / min and held for 6-7h. After baking, the kiln is allowed to cool down to room temperature naturally to obtain corrosion-resistant castable.
[0014] In step (1), the stirring speed before adding polypropylene explosion-proof fiber is 55-65 r / min, and the stirring speed is adjusted to 30-35 r / min after adding polypropylene explosion-proof fiber.
[0015] In step (2), the mass of deionized water is 5.3-5.7% of the mass of the dry mixture.
[0016] The vibration molding time in step (3) is 2-4 minutes.
[0017] In step (3), the static curing temperature is 25-30℃, the relative humidity during static curing is 91-93%, and the static curing time is 50-52h.
[0018] The corrosion-resistant castable prepared in step (4) is an unburned product. When it is applied to the skimmer at the end of the main iron trough, it undergoes ceramic sintering at the service temperature to form a dense ceramic bond phase.
[0019] Compared with the prior art, the present invention has the following advantages: (1) The corrosion-resistant castable of the present invention uses waste corundum-spinel refractory castable complexes of different particle sizes and a small amount of pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm as aggregates, pretreated secondary alumina ash with a particle size of ≤ 0.088mm and pretreated titanium-containing blast furnace slag as powders, a complex of calcium zirconate, cerium aluminate and lanthanum tantalate as anti-slag agent, a complex of p-Al2O3 micro powder and pseudoboehmite powder as cementless binder, citric acid as retarder, zirconium oxide to improve the thermal shock stability of the material, polypropylene explosion-proof fiber as explosion-proof component, and polycarboxylate superplasticizer to improve the construction fluidity of the castable and reduce the amount of water added during molding. Thus, the raw materials complement each other, so that the prepared castable has excellent high-temperature strength and corrosion resistance during service.
[0020] (2) The corrosion-resistant castable of the present invention uses multi-stage particle size-matched waste corundum-spinel refractory castable and a small amount of pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm as aggregate. Large-particle waste corundum-spinel refractory castable forms the material skeleton, giving the castable volume stability and resistance to molten iron erosion; medium-particle waste corundum-spinel refractory castable fills the gaps between the large aggregates, achieving close particle packing, reducing the internal porosity of the castable, and reducing the penetration of molten slag into the matrix. The fine-grained waste corundum-spinel refractory castable is used in combination with a small amount of pretreated titanium-containing blast furnace slag. The perovskite (CaTiO3) microcrystals carried by the pretreated titanium-containing blast furnace slag are distributed as a dispersed hard phase at the interface between the matrix and aggregate, which can play a grain boundary pinning role and inhibit abnormal growth of matrix grains at service temperature. The waste corundum-spinel refractory castable itself contains corundum and magnesium aluminum spinel phases. Corundum has a high melting point and excellent mechanical strength, while magnesium aluminum spinel has excellent resistance to alkaline slag erosion and can resist the chemical erosion of blast furnace iron slag.
[0021] (3) The corrosion-resistant castable of the present invention uses pretreated secondary aluminum ash and pretreated titanium-containing blast furnace slag as powder. The main phase of the pretreated secondary aluminum ash is alumina, which has high activity. On the one hand, it fills the gaps between aggregates and optimizes the matrix packing density. On the other hand, it reacts with MgO in the matrix at high temperature to generate in-situ magnesium aluminum spinel, which promotes the sintering and densification of the matrix. The titanium in the titanium-containing blast furnace slag is mainly present in the form of high-melting-point perovskite (CaTiO3), which is dispersed in the matrix to form an inert barrier. When in service, the temperature of the slag penetration front decreases, and high-melting-point crystalline phases such as perovskite and magnesium aluminum spinel precipitate, which makes the slag thicker and self-blocking, further occupying the penetration channels, thereby playing an auxiliary role in resisting penetration.
[0022] (4) The corrosion-resistant castable of the present invention uses calcium zirconate, cerium aluminate, and lanthanum tantalate as anti-slag agents, which can work synergistically. Among them, calcium zirconate has a high melting point and excellent chemical stability. It does not easily react with iron hook slag at high temperature. It is a calcium-saturated phase and does not easily react with CaO in the slag to form a low-melting-point phase. It can inhibit the diffusion of metal ions such as Fe and Mn in the slag into the matrix. Cerium aluminate is a rare earth aluminate. At high temperature, it can react with SiO2, CaO, etc. that penetrate into the slag to form high-viscosity rare earth aluminosilicates, which increases the viscosity of the slag and reduces the slag penetration rate. At the same time, rare earth ions can be enriched at the spinel grain boundaries, inhibiting abnormal grain growth at high temperature and maintaining the high-temperature strength of the fine-grained structure of the matrix. Lanthanum tantalate has a high melting point and good chemical stability. It does not easily react with iron trough slag at high temperature. It can be dispersed in the matrix as an inert high-melting-point filler. It can hinder the slag penetration path through the physical barrier effect and destroy the continuous formation of the low-melting-point silicate phase. The three components, when combined, form a multi-layered anti-slag protection system consisting of "chemical seepage barrier, viscosity enhancement and rate reduction, and physical barrier".
[0023] (5) The corrosion-resistant castable of the present invention uses a mixture of ρ-Al2O3 micro powder and pseudoboehmite powder as a binder. ρ-Al2O3 micro powder undergoes a hydration reaction upon contact with water, mainly generating gibbsite and boehmite gels, providing early hydration strength for the castable and ensuring the demolding strength of the green body. Pseudoboehmite has a high specific surface area and colloidal activity, and can disperse in water to form a high-viscosity colloidal substance. Its nanoscale flakes are bridged with matrix particles by hydrogen bonds through surface hydroxyl groups and physically fill the gaps between aggregates, improving the uniformity and density of the green body. During the low-temperature baking stage (≤450℃), the hydration products of ρ-Al2O3 and pseudoboehmite simultaneously dehydrate and transform into active alumina. During subsequent service, as the kiln temperature rises to 1300-1550℃, the activated alumina undergoes solid-state sintering with the Al2O3, MgO, and active components in the secondary alumina ash matrix, promoting matrix ceramization and forming a dense high-temperature ceramic bond, thus improving the material's high-temperature structural strength and corrosion resistance. Furthermore, trace amounts of citric acid are added to the formula as a retarder, which, by adsorbing onto the surface of p-Al2O3 microparticles, delays the nucleation of hydration products, extends the workability of the castable, and ensures sufficient vibration molding and venting of the preforms.
[0024] (6) The corrosion-resistant castable of the present invention also contains polypropylene explosion-proof fiber, zirconium oxide, and polycarboxylate superplasticizer in its raw materials. During the baking and heating stage, the polypropylene explosion-proof fiber leaves interconnected venting channels in situ inside the green body. These channels remain unobstructed during subsequent heating, allowing the steam generated by the vaporization of free and bound water within the green body to be smoothly discharged, significantly reducing internal steam pressure and effectively preventing the thick, large skimmer preforms from bursting during baking. Zirconia improves thermal shock stability by hindering crack propagation through phase transformation expansion at the crack tip and reducing the material's elastic modulus. The polycarboxylate superplasticizer disperses inorganic particles through electrostatic repulsion and steric hindrance effects, imparting good fluidity to the castable slurry under low water addition conditions, reducing the amount of water required for molding, decreasing the source of pores inside the green body, and improving the density and high-temperature performance of the castable.
[0025] (7) The preparation method of the corrosion-resistant castable of the present invention achieves uniform dispersion of solid waste aggregate, ultrafine powder and functional additives through graded feeding and variable speed stirring, thus protecting the integrity of the explosion-proof fiber structure; low-water gel molding is used to improve the density of the green body, and long-term mold curing is combined to ensure that the cement-free gel system is fully hardened, avoiding demolding defects of large precast parts; and the water vapor pressure is released step by step through multi-stage gradient baking, thus completely solving the problem of baking cracking of thick precast parts. Therefore, the synergistic effect between the various process steps ensures the stable performance of the prepared corrosion-resistant castable. Detailed Implementation
[0026] Example 1
[0027] The corrosion-resistant castable described in Example 1 is composed of the following raw materials by weight: 14 parts of waste corundum-spinel refractory castable with a particle size of 8mm < ≤ 15mm, 16 parts of waste corundum-spinel refractory castable with a particle size of 5mm < ≤ 8mm, 15 parts of waste corundum-spinel refractory castable with a particle size of 3mm < ≤ 5mm, 13 parts of waste corundum-spinel refractory castable with a particle size of 1mm < ≤ 3mm, and 0.088mm < ≤ 1mm waste corundum-spinel refractory castable. The composition includes: 10 parts of raw material, 6 parts of pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm, 4.7 parts of pretreated titanium-containing blast furnace slag with a particle size of ≤ 0.088mm, 9.0 parts of pretreated secondary aluminum ash with a particle size of ≤ 0.088mm, 2.0 parts of calcium zirconate, 1.6 parts of cerium aluminate, 1.4 parts of lanthanum tantalate, 5.5 parts of p-Al2O3 micro powder, 2.9 parts of pseudoboehmite powder, 0.045 parts of citric acid, 0.23 parts of polypropylene explosion-proof fiber, 2.9 parts of zirconium oxide, and 0.21 parts of polycarboxylate superplasticizer.
[0028] The waste corundum-spinel refractory castable, by mass percentage, has the following chemical composition: Al2O3 83.98%, MgO 10.32%, SiO2 2.09%, Fe2O3 0.95%, Na2O 0.87%, CaO 0.81%, K2O 0.04%, SO3 0.02%, and loss on ignition 0.92%.
[0029] The preparation method of pretreated titanium-containing blast furnace slag consists of the following steps: crushing the titanium-containing blast furnace slag to a particle size ≤15mm, removing iron through magnetic separation, then placing it in an air-atmosphere resistance furnace, heating it from room temperature to 800℃ at a heating rate of 5℃ / min and holding it at that temperature for 1h, cooling it to room temperature with the furnace, and preparing the pretreated titanium-containing blast furnace slag by two-stage sieving: 0.088mm < particle size ≤1mm and particle size ≤0.088mm.
[0030] Wherein: the titanium-containing blast furnace slag is an industrial solid waste generated during the smelting of vanadium-titanium magnetite, and its chemical composition by mass percentage is as follows: CaO 28.02%, SiO2 22.54%, TiO2 21.62%, Al2O3 14.10%, MgO 10.03%, FeO 1.31%, MnS 1.26%, V2O5 0.72%, and loss on ignition 0.40%.
[0031] The preparation method of pretreated secondary aluminum ash consists of the following steps: ① The secondary aluminum ash is placed in an air-atmosphere resistance furnace and heated from room temperature to 1050℃ at a heating rate of 5℃ / min, and held at that temperature for 2.5h, and then cooled to 25℃ with the furnace; ② The cooled calcined product is added to hot water at 85℃ with a solid-liquid mass ratio of 1:2.5, and stirred for 100min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ③ Hot water at 85℃ is added to the filter cake obtained in step ② with a solid-liquid mass ratio of 1:2.5, and stirred for 75min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ④ Hot water at 85℃ is added to the filter cake obtained in step ③ with a solid-liquid mass ratio of 1:3.0, and stirred for 80min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ⑤ The filter cake obtained in step ④ is dried at 110℃ under forced air for 12h, and then passed through a 180-mesh sieve to prepare pretreated secondary aluminum ash.
[0032] The secondary aluminum ash, by mass percentage, has the following chemical composition: Al₂O₃ 86.32%, MgO 8.42%, SiO₂ 1.34%, CaO 1.00%, K₂O 0.88%, Fe₂O₃ 0.29%, MnO 0.28%, Na₂O 0.24%, P₂O₅ 0.11%, TiO₂ 0.13%, and loss on ignition 0.99%.
[0033] The preparation method of the corrosion-resistant castable described in Example 1 consists of the following steps: (1) Waste corundum-spinel refractory castable with particle size ≤ 15mm, waste corundum-spinel refractory castable with particle size ≤ 8mm, waste corundum-spinel refractory castable with particle size ≤ 5mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, and waste corundum-spinel refractory castable with particle size ≤ 0.088mm. Waste corundum-spinel refractory castable recycled material and pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm were added to a forced mixer and dry-mixed for 85s to make it uniform. Then, pretreated secondary alumina ash with a particle size of ≤ 0.088mm and pretreated titanium-containing blast furnace slag with a particle size of ≤ 0.088mm, calcium zirconate, cerium aluminate, lanthanum tantalate, p-Al2O3 micro powder, boehmite powder, zirconium oxide, citric acid and polycarboxylate superplasticizer were added and dry-mixed for 1.7min. Finally, polypropylene explosion-proof fiber was added and dry-mixed for 25s to prepare a dry mixture. (2) Add deionized water to the dry mixture prepared in step (1) and continue stirring for 4 minutes to obtain the casting slurry; (3) The prepared grout is injected into the precast mold, placed on a vibrating table for vibration molding, then allowed to stand for curing, and finally demolded. (4) The demolded preforms are sent into a baking kiln for segmented gradient baking. First, the temperature is raised to 110℃ at a heating rate of 0.9℃ / min and held for 13h. Then, the temperature is raised to 220℃ at a heating rate of 1.1℃ / min and held for 7h. After that, the temperature is raised to 450℃ at a heating rate of 1.4℃ / min and held for 6.5h. After baking, the kiln is naturally cooled to room temperature to prepare corrosion-resistant castable.
[0034] In step (1), the stirring speed is 60 r / min before adding polypropylene explosion-proof fiber, and the stirring speed is adjusted to 32 r / min after adding polypropylene explosion-proof fiber.
[0035] In step (2), the mass of deionized water is 5.7% of the mass of the dry mixture.
[0036] The vibration molding time in step (3) is 3 minutes.
[0037] In step (3), the static curing temperature is 27℃, the relative humidity during static curing is 92%, and the static curing time is 51h.
[0038] The corrosion-resistant castable prepared in step (4) is an unburned product. When it is applied to the skimmer at the end of the main iron trough, it undergoes ceramic sintering at the service temperature to form a dense ceramic bond phase.
[0039] Example 2
[0040] The corrosion-resistant castable described in Example 2 is composed of the following raw materials by weight: 13 parts of waste corundum-spinel refractory castable with a particle size of 8mm < ≤ 15mm, 17 parts of waste corundum-spinel refractory castable with a particle size of 5mm < ≤ 8mm, 14 parts of waste corundum-spinel refractory castable with a particle size of 3mm < ≤ 5mm, 14 parts of waste corundum-spinel refractory castable with a particle size of 1mm < ≤ 3mm, and 0.088mm < ≤ 1mm waste corundum-spinel refractory castable. 9 parts of pretreated titanium-containing blast furnace slag (0.088mm < particle size ≤ 1mm), 7 parts of pretreated titanium-containing blast furnace slag (0.088mm < particle size ≤ 1mm), 4.5 parts of pretreated titanium-containing blast furnace slag (0.088mm < particle size ≤ 0.088mm), 9.5 parts of pretreated secondary aluminum ash (0.088mm < particle size ≤ 0.088mm), 1.9 parts of calcium zirconate, 1.7 parts of cerium aluminate, 1.3 parts of lanthanum tantalate, 5.3 parts of p-Al2O3 micro powder, 3.1 parts of pseudoboehmite powder, 0.04 parts of citric acid, 0.22 parts of polypropylene explosion-proof fiber, 2.7 parts of zirconium oxide, and 0.18 parts of polycarboxylate superplasticizer.
[0041] The waste corundum-spinel refractory castable, by mass percentage, has the following chemical composition: Al2O3 83.98%, MgO 10.32%, SiO2 2.09%, Fe2O3 0.95%, Na2O 0.87%, CaO 0.81%, K2O 0.04%, SO3 0.02%, and loss on ignition 0.92%.
[0042] The preparation method of pretreated titanium-containing blast furnace slag consists of the following steps: crushing the titanium-containing blast furnace slag to a particle size ≤15mm, removing iron through magnetic separation, then placing it in an air-atmosphere resistance furnace, heating it from room temperature to 800℃ at a heating rate of 5℃ / min and holding it at that temperature for 1h, cooling it to room temperature with the furnace, and preparing the pretreated titanium-containing blast furnace slag by two-stage sieving: 0.088mm < particle size ≤1mm and particle size ≤0.088mm.
[0043] Wherein: the titanium-containing blast furnace slag is an industrial solid waste generated during the smelting of vanadium-titanium magnetite, and its chemical composition by mass percentage is as follows: CaO 28.02%, SiO2 22.54%, TiO2 21.62%, Al2O3 14.10%, MgO 10.03%, FeO 1.31%, MnS 1.26%, V2O5 0.72%, and loss on ignition 0.40%.
[0044] The preparation method of pretreated secondary aluminum ash consists of the following steps: ① The secondary aluminum ash is placed in an air-atmosphere resistance furnace and heated from room temperature to 1050℃ at a heating rate of 5℃ / min, and held at that temperature for 2.5h, and then cooled to 25℃ with the furnace; ② The cooled calcined product is added to hot water at 85℃ with a solid-liquid mass ratio of 1:2.5, and stirred for 100min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ③ Hot water at 85℃ is added to the filter cake obtained in step ② with a solid-liquid mass ratio of 1:2.5, and stirred for 75min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ④ Hot water at 85℃ is added to the filter cake obtained in step ③ with a solid-liquid mass ratio of 1:3.0, and stirred for 80min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ⑤ The filter cake obtained in step ④ is dried at 110℃ under forced air for 12h, and then passed through a 180-mesh sieve to prepare pretreated secondary aluminum ash.
[0045] The secondary aluminum ash, by mass percentage, has the following chemical composition: Al₂O₃ 86.32%, MgO 8.42%, SiO₂ 1.34%, CaO 1.00%, K₂O 0.88%, Fe₂O₃ 0.29%, MnO 0.28%, Na₂O 0.24%, P₂O₅ 0.11%, TiO₂ 0.13%, and loss on ignition 0.99%.
[0046] The preparation method of the corrosion-resistant castable described in Example 2 consists of the following steps: (1) Waste corundum-spinel refractory castable with particle size ≤ 15mm, waste corundum-spinel refractory castable with particle size ≤ 8mm, waste corundum-spinel refractory castable with particle size ≤ 5mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, and waste corundum-spinel refractory castable with particle size ≤ 0.088mm. Waste corundum-spinel refractory castable recycled material and pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm were added to a forced mixer and dry-mixed for 90s to make it uniform. Then, pretreated secondary alumina ash with a particle size of ≤ 0.088mm and pretreated titanium-containing blast furnace slag with a particle size of ≤ 0.088mm, calcium zirconate, cerium aluminate, lanthanum tantalate, p-Al2O3 micro powder, pseudoboehmite powder, zirconium oxide, citric acid and polycarboxylate superplasticizer were added and dry-mixed for 1.5min. Finally, polypropylene explosion-proof fiber was added and dry-mixed for 20s to prepare a dry mixture. (2) Add deionized water to the dry mixture prepared in step (1) and continue stirring for 3 minutes to obtain the casting slurry; (3) The prepared grout is injected into the precast mold, placed on a vibrating table for vibration molding, then allowed to stand for curing, and finally demolded. (4) The demolded preforms are sent into a baking kiln for segmented gradient baking. First, the temperature is raised to 110℃ at a heating rate of 0.8℃ / min and held for 12h. Then, the temperature is raised to 220℃ at a heating rate of 1.0℃ / min and held for 8h. After that, the temperature is raised to 450℃ at a heating rate of 1.3℃ / min and held for 6h. After baking, the kiln is naturally cooled to room temperature to prepare corrosion-resistant castable.
[0047] In step (1), the stirring speed is 65 r / min before adding polypropylene explosion-proof fiber, and the stirring speed is adjusted to 30 r / min after adding polypropylene explosion-proof fiber.
[0048] In step (2), the mass of deionized water is 5.5% of the mass of the dry mixture.
[0049] The vibration molding time in step (3) is 2 minutes.
[0050] In step (3), the static curing temperature is 25℃, the relative humidity during static curing is 93%, and the static curing time is 52h.
[0051] The corrosion-resistant castable prepared in step (4) is an unburned product. When it is applied to the skimmer at the end of the main iron trough, it undergoes ceramic sintering at the service temperature to form a dense ceramic bond phase.
[0052] Example 3
[0053] The corrosion-resistant castable described in Example 3 is composed of the following raw materials by weight: 15 parts of waste corundum-spinel refractory castable with a particle size of 8mm < ≤ 15mm, 15 parts of waste corundum-spinel refractory castable with a particle size of 5mm < ≤ 8mm, 16 parts of waste corundum-spinel refractory castable with a particle size of 3mm < ≤ 5mm, 12 parts of waste corundum-spinel refractory castable with a particle size of 1mm < ≤ 3mm, and 0.088mm < ≤ 1mm of waste corundum-spinel refractory castable. 11 parts of pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm, 5 parts of pretreated titanium-containing blast furnace slag with a particle size of ≤ 0.088mm, 8.5 parts of pretreated secondary aluminum ash with a particle size of ≤ 0.088mm, 2.1 parts of calcium zirconate, 1.5 parts of cerium aluminate, 1.5 parts of lanthanum tantalate, 5.7 parts of p-Al2O3 micro powder, 2.7 parts of pseudoboehmite powder, 0.05 parts of citric acid, 0.24 parts of polypropylene explosion-proof fiber, 3.1 parts of zirconium oxide, and 0.23 parts of polycarboxylate superplasticizer.
[0054] The waste corundum-spinel refractory castable, by mass percentage, has the following chemical composition: Al2O3 83.98%, MgO 10.32%, SiO2 2.09%, Fe2O3 0.95%, Na2O 0.87%, CaO 0.81%, K2O 0.04%, SO3 0.02%, and loss on ignition 0.92%.
[0055] The preparation method of pretreated titanium-containing blast furnace slag consists of the following steps: crushing the titanium-containing blast furnace slag to a particle size ≤15mm, removing iron through magnetic separation, then placing it in an air-atmosphere resistance furnace, heating it from room temperature to 800℃ at a heating rate of 5℃ / min and holding it at that temperature for 1h, cooling it to room temperature with the furnace, and preparing the pretreated titanium-containing blast furnace slag by two-stage sieving: 0.088mm < particle size ≤1mm and particle size ≤0.088mm.
[0056] Wherein: the titanium-containing blast furnace slag is an industrial solid waste generated during the smelting of vanadium-titanium magnetite, and its chemical composition by mass percentage is as follows: CaO 28.02%, SiO2 22.54%, TiO2 21.62%, Al2O3 14.10%, MgO 10.03%, FeO 1.31%, MnS 1.26%, V2O5 0.72%, and loss on ignition 0.40%.
[0057] The preparation method of pretreated secondary aluminum ash consists of the following steps: ① The secondary aluminum ash is placed in an air-atmosphere resistance furnace and heated from room temperature to 1050℃ at a heating rate of 5℃ / min, and held at that temperature for 2.5h, and then cooled to 25℃ with the furnace; ② The cooled calcined product is added to hot water at 85℃ with a solid-liquid mass ratio of 1:2.5, and stirred for 100min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ③ Hot water at 85℃ is added to the filter cake obtained in step ② with a solid-liquid mass ratio of 1:2.5, and stirred for 75min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ④ Hot water at 85℃ is added to the filter cake obtained in step ③ with a solid-liquid mass ratio of 1:3.0, and stirred for 80min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ⑤ The filter cake obtained in step ④ is dried at 110℃ under forced air for 12h, and then passed through a 180-mesh sieve to prepare pretreated secondary aluminum ash.
[0058] The secondary aluminum ash, by mass percentage, has the following chemical composition: Al₂O₃ 86.32%, MgO 8.42%, SiO₂ 1.34%, CaO 1.00%, K₂O 0.88%, Fe₂O₃ 0.29%, MnO 0.28%, Na₂O 0.24%, P₂O₅ 0.11%, TiO₂ 0.13%, and loss on ignition 0.99%.
[0059] The preparation method of the corrosion-resistant castable described in Example 3 consists of the following steps: (1) Waste corundum-spinel refractory castable with particle size ≤ 15mm, waste corundum-spinel refractory castable with particle size ≤ 8mm, waste corundum-spinel refractory castable with particle size ≤ 5mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, and waste corundum-spinel refractory castable with particle size ≤ 0.088mm. Waste corundum-spinel refractory castable recycled material and pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm were added to a forced mixer and dry-mixed for 80s to make it uniform. Then, pretreated secondary alumina ash with a particle size of ≤ 0.088mm and pretreated titanium-containing blast furnace slag with a particle size of ≤ 0.088mm, calcium zirconate, cerium aluminate, lanthanum tantalate, p-Al2O3 micro powder, boehmite powder, zirconium oxide, citric acid and polycarboxylate superplasticizer were added and dry-mixed for 2.0min. Finally, polypropylene explosion-proof fiber was added and dry-mixed for 30s to prepare a dry mixture. (2) Add deionized water to the dry mixture prepared in step (1) and continue stirring for 5 minutes to obtain the casting slurry; (3) The prepared grout is injected into the precast mold, placed on a vibrating table for vibration molding, then allowed to stand for curing, and finally demolded. (4) The demolded preforms are sent into a baking kiln for segmented gradient baking. First, the temperature is raised to 110℃ at a heating rate of 1.0℃ / min and held for 14h. Then, the temperature is raised to 220℃ at a heating rate of 1.2℃ / min and held for 6h. After that, the temperature is raised to 450℃ at a heating rate of 1.5℃ / min and held for 7h. After baking, the kiln is naturally cooled to room temperature to prepare corrosion-resistant castable.
[0060] In step (1), the stirring speed is 55 r / min before adding polypropylene explosion-proof fiber, and the stirring speed is adjusted to 35 r / min after adding polypropylene explosion-proof fiber.
[0061] In step (2), the mass of deionized water is 5.3% of the mass of the dry mixture.
[0062] The vibration molding time in step (3) is 4 minutes.
[0063] In step (3), the static curing temperature is 30℃, the relative humidity during static curing is 91%, and the static curing time is 50h.
[0064] The corrosion-resistant castable prepared in step (4) is an unburned product. When it is applied to the skimmer at the end of the main iron trough, it undergoes ceramic sintering at the service temperature to form a dense ceramic bond phase.
[0065] Comparative Example 1 The preparation method of the corrosion-resistant castable described in Comparative Example 1 is the same as that in Example 1. The only difference is that calcium zirconate is not added to the raw materials, while the types and amounts of the other raw materials are the same as in Example 1.
[0066] Comparative Example 2 The preparation method of the corrosion-resistant castable described in Comparative Example 2 is the same as that in Example 1. The only difference is that cerium aluminate is not added to the raw materials, while the types and amounts of the other raw materials are the same as in Example 1.
[0067] Comparative Example 3 The preparation method of the corrosion-resistant castable described in Comparative Example 3 is the same as that in Example 1. The only difference is that lanthanum tantalate is not added to the raw materials, while the types and amounts of the other raw materials are the same as in Example 1.
[0068] Performance tests were conducted on the corrosion-resistant castables prepared in Examples 1-3 and Comparative Examples 1-3. Apparent porosity was tested according to YB / T 5200; room temperature compressive strength was tested according to GB / T 5072; room temperature flexural strength was tested according to GB / T 3001; room temperature compressive strength after firing at 1450℃ was tested according to GB / T 5072 after pre-firing at 1450℃ for 3 hours and then cooled to 25℃ in the furnace; room temperature flexural strength after firing at 1450℃ was tested according to GB / T 3001 after pre-firing at 1450℃ for 3 hours and then cooled to 25℃ in the furnace; static slag resistance was tested using crucible samples baked at 450℃, filled with molten slag, and then tested according to GB / T The static crucible method, as specified in 8931 "Test Method for Slag Resistance of Refractory Materials", was used. The test temperature was 1450℃, and the holding time was 3 hours. Molten slag from the blast furnace skimmer was used as the erosion medium. The slag erosion depth and penetration depth of the samples were tested. The results are shown in Table 1 below. Table 1. Test results of corrosion-resistant castables in Examples 1-3 and Comparative Examples 1-3
[0069] As shown in Table 1, the corrosion-resistant castables prepared in Examples 1-3 have significantly better performance than those in Comparative Examples 1-3. In Comparative Examples 1-3, the absence of any one of the anti-slag agents calcium zirconate, cerium aluminate, and lanthanum tantalate resulted in the corrosion-resistant castables prepared in Examples 1-3 having significantly greater anti-slag erosion depth and anti-slag penetration depth than those in Examples 1-3.
[0070] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A corrosion-resistant castable, characterized in that: The refractory castable, by weight, consists of the following raw materials: 13-15 parts of waste corundum-spinel refractory castable with a particle size of 8mm < ≤ 15mm; 15-17 parts of waste corundum-spinel refractory castable with a particle size of 5mm < ≤ 8mm; 14-16 parts of waste corundum-spinel refractory castable with a particle size of 3mm < ≤ 5mm; 12-14 parts of waste corundum-spinel refractory castable with a particle size of 1mm < ≤ 3mm; 9-11 parts of waste corundum-spinel refractory castable with a particle size of 0.088mm < ≤ 1mm; and pretreated waste corundum containing... The composition includes: 5-7 parts titanium blast furnace slag, 4.5-5.0 parts pretreated titanium-containing blast furnace slag with a particle size ≤0.088mm, 8.5-9.5 parts pretreated secondary alumina ash with a particle size ≤0.088mm, 1.9-2.1 parts calcium zirconate, 1.5-1.7 parts cerium aluminate, 1.3-1.5 parts lanthanum tantalate, 5.3-5.7 parts p-Al2O3 micro powder, 2.7-3.1 parts pseudoboehmite powder, 0.04-0.05 parts citric acid, 0.22-0.24 parts polypropylene explosion-proof fiber, 2.7-3.1 parts zirconium oxide, and 0.18-0.23 parts polycarboxylate superplasticizer.
2. The corrosion-resistant castable according to claim 1, characterized in that: The waste corundum-spinel refractory castable has the following chemical composition by mass percentage: Al2O3 83.98%, MgO 10.32%, SiO2 2.09%, Fe2O3 0.95%, Na2O 0.87%, CaO 0.81%, K2O 0.04%, SO3 0.02%, and loss on ignition 0.92%.
3. The corrosion-resistant castable according to claim 1, characterized in that: The preparation method of pretreated titanium-containing blast furnace slag consists of the following steps: crushing the titanium-containing blast furnace slag to a particle size ≤15mm, removing iron through magnetic separation, then placing it in an air-atmosphere resistance furnace, heating it from room temperature to 800℃ at a heating rate of 5℃ / min and holding it at that temperature for 1h, cooling it to room temperature with the furnace, and preparing the pretreated titanium-containing blast furnace slag by two-stage sieving: 0.088mm < particle size ≤1mm and particle size ≤0.088mm.
4. The corrosion-resistant castable according to claim 3, characterized in that: The titanium-containing blast furnace slag is an industrial solid waste generated during the smelting of vanadium-titanium magnetite. Its chemical composition by mass percentage is as follows: CaO 28.02%, SiO2 22.54%, TiO2 21.62%, Al2O3 14.10%, MgO 10.03%, FeO 1.31%, MnS 1.26%, V2O5 0.72%, and loss on ignition 0.40%.
5. The corrosion-resistant castable according to claim 1, characterized in that: The preparation method of pretreated secondary aluminum ash consists of the following steps: ① The secondary aluminum ash is placed in an air-atmosphere resistance furnace and heated from room temperature to 1050℃ at a heating rate of 5℃ / min, and held at that temperature for 2.5h, and then cooled to 25℃ with the furnace; ② The cooled calcined product is added to hot water at 85℃ with a solid-liquid mass ratio of 1:2.5, and stirred for 100min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ③ Hot water at 85℃ is added to the filter cake obtained in step ② with a solid-liquid mass ratio of 1:2.5, and stirred for 75min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ④ Hot water at 85℃ is added to the filter cake obtained in step ③ with a solid-liquid mass ratio of 1:3.0, and stirred for 80min for hydrolysis. After hydrolysis, the solid-liquid is separated by pressure filtration, and the filter cake is collected; ⑤ The filter cake obtained in step ④ is dried at 110℃ under forced air for 12h, and then passed through a 180-mesh sieve to prepare pretreated secondary aluminum ash.
6. The corrosion-resistant castable according to claim 5, characterized in that: The secondary aluminum ash, by mass percentage, has the following chemical composition: Al2O3 86.32%, MgO 8.42%, SiO2 1.34%, CaO 1.00%, K2O 0.88%, Fe2O3 0.29%, MnO 0.28%, Na2O 0.24%, P2O5 0.11%, TiO2 0.13%, and loss on ignition 0.99%.
7. A method for preparing the corrosion-resistant castable according to claim 1, characterized in that: It consists of the following steps: (1) Waste corundum-spinel refractory castable with particle size ≤ 15mm, waste corundum-spinel refractory castable with particle size ≤ 8mm, waste corundum-spinel refractory castable with particle size ≤ 5mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, waste corundum-spinel refractory castable with particle size ≤ 3mm, and waste corundum-spinel refractory castable with particle size ≤ 0.088mm. Waste corundum-spinel refractory castable recycled material and pretreated titanium-containing blast furnace slag with a particle size of 0.088mm < ≤ 1mm are added to a forced mixer and dry-mixed for 80-90s to ensure uniform mixing. Then, pretreated secondary alumina ash with a particle size of ≤ 0.088mm and pretreated titanium-containing blast furnace slag with a particle size of ≤ 0.088mm, calcium zirconate, cerium aluminate, lanthanum tantalate, p-Al2O3 micro powder, pseudoboehmite powder, zirconium oxide, citric acid and polycarboxylate superplasticizer are added and dry-mixed for 1.5-2.0min. Finally, polypropylene explosion-proof fiber is added and dry-mixed for 20-30s to prepare a dry mixture. (2) Add deionized water to the dry mixture prepared in step (1) and continue stirring for 3-5 minutes to obtain the casting slurry; (3) The prepared grout is injected into the precast mold, placed on a vibrating table for vibration molding, then allowed to stand for curing, and finally demolded. (4) The demolded preforms are sent into a baking kiln for segmented gradient baking. First, the temperature is raised to 110℃ at a heating rate of 0.8-1.0℃ / min and held for 12-14h. Then, the temperature is raised to 220℃ at a heating rate of 1.0-1.2℃ / min and held for 6-8h. After that, the temperature is raised to 450℃ at a heating rate of 1.3-1.5℃ / min and held for 6-7h. After baking, the kiln is allowed to cool down to room temperature naturally to obtain corrosion-resistant castable.
8. The method for preparing the corrosion-resistant castable according to claim 7, characterized in that: In step (1), the stirring speed is 55-65 r / min before adding polypropylene explosion-proof fiber, and the stirring speed is adjusted to 30-35 r / min after adding polypropylene explosion-proof fiber.
9. The method for preparing the corrosion-resistant castable according to claim 7, characterized in that: In step (2), the mass of deionized water is 5.3-5.7% of the mass of the dry mixture.
10. The method for preparing the corrosion-resistant castable according to claim 7, characterized in that: The vibration molding time in step (3) is 2-4 minutes; In step (3), the static curing temperature is 25-30℃, the relative humidity during static curing is 91-93%, and the static curing time is 50-52h.